Saudi Arabia and Indonesian Networks: On Islamic and Muslim Scholars - Sumanto Al Qurtuby (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2021)
This article studies Saudi Arabia–trained Indonesian Islamic scholars, both past and present. It also discusses Saudi Arabia’s non-Islamic studies Indonesian Muslim scholars. Since past centuries, Muslims on the Malay–Indonesian archipelago has journeyed to the Arabian Peninsula, especially Hijaz, either for pilgrimage or learning. This legacy continues nowadays. While many alumni of Saudi Arabia’s Islamic educational institutions–formal and informal–have contributed significantly to the development of Islamic and Muslim cultures and education in Indonesia, some chose to stay, teach, and pass away in Makkah. The study shows that, unlike popular beliefs and opinions, Saudi Arabia-trained Indonesian Islamic scholars vary in terms of religious orientations, political affiliations, social networks, and academic backgrounds. For example, some scholars tend to be ultraconservative and militant, while others are inclined to be progressive and moderate. While the presence of Indonesian Islamic scholars has declined significantly in Saudi Arabia since the last four decades, new tiny Indonesian Muslim scholars specializing in non-Islamic studies began to emerge and teach in some universities in the Kingdom. This article, among others, aims at examining the plurality, complexity, and shifting dynamics of Saudi Arabia’s Indonesian Islamic and Muslim scholars as well as their major roles and contributions in the spread and development of Indonesia’s Islam and society.